The experiences of NGO-employed HIV caregivers in peri-urban informal settlements, South Africa. - Kemble, Veronica (My University, 2011)
Caregivers comprise a unique population of people who devote much of their time to the ill people whom they serve. This study aimed to examine the complex experiences of NGO-employed HIV caregivers in peri-urban informal settlements. This study provides an overview of the literature pertaining to NGO-employed HIV caregivers. Due to the fact that the caregivers who participated in this study worked for a faith-based organisation, this study examined the possible role of religiosity in influencing the experiences of the caregivers. Twelve in depth, semi-structured interviews were conducted with NGO-employed HIV caregivers who worked for a faith-based (Christian) organisation. Thematic content analysis was used to analyse data generated by the interviews. Religiosity is common to the majority of the themes identified, and seems to play an important role in the way in which the caregivers cope with stress, the way that they treat their patients, the way that caregivers perveive people in informal settlements to think about HIV, as well as the way in which they feel that communities within informal settlements think about and deal with HIV. The results of this study have various implications for future research, theory and policy regarding HIV caregivers, home-based care in South Africa, as well as the possible role of faith-based organisations in assisting with the HIV pandemic.